Weakly progressive: Disproportionate higher education attendance and the structure of income taxes - Michele Gubello; Nora Margot Strecker (University College Dublin, UCD School of Economics, 2022)
This paper studies the effect of income tax progressivity on the disproportionate usage of publicly funded higher education. We develop a rational choice model showing that more progressive tax systems increase poorer households' net fiscal benefit, making their children more likely to attend university. The model also shows that weakly progressive tax systems can determine a "perverse redistribution", in which poorer households subsidize the higher education for richer households. With this model, we develop three empirically testable hypotheses, where (i) countries with higher levels of progressivity have higher enrollment rate in higher education; (ii) the parental income gradient in children's higher education attendance is lower in countries with more progressive tax systems; and (iii) countries with more progressive tax systems have a lower perverse redistribution in higher education. The model also analyzes the role of local progressivity in higher education choice and redistribution. We provide empirical validation for our model's conclusions across European-OECD countries.
Keywords: I23; H41; H31; H24; 330; Public Higher Education; Progressive Income Tax; University Choice; Inequality